Effects of trans-mitral flow patterns and heart rate on intraventricular pressure gradients and E/E’ in the early stage of a rat model of hypertensive cardiomyopathy - Hirose, Miki; Ma, Danfu; Shimada, Kazumi; Yoshida, Tomohiko; Matsuura, Katsuhiro; Kitpipatkun, Pitipat; Hatanaka, Akari; Zhao, Yanbing; Takahashi, Ken; Tanaka, Ryou; Hamabe, Lina (Frontiers in Veterinary Science, 2025)
BackgroundThe mitral inflow spectral is expressed as two separate waves: early diastolic trans-mitral flow velocity (E) and late diastolic trans-mitral flow velocity (A) waves. When the heart rate (HR) increases and the diastolic time diminishes, the mitral flow pattern changes from EA-separation to EA-fusion. The E wave provides information about preload and diastolic function. Tissue Doppler imaging (TDI) and non-invasive intraventricular pressure gradient (IVPG) based on color-M-mode echocardiography are two techniques established in recent years with good repeatability in cardiac function evaluation, especially diastolic.Hypothesis/objectiveWe hypothesize that IVPG and E/E’ are differentially influenced by mitral inflow patterns.AnimalsA total of 66 hypertensive cardiomyopathy (HTN-CM) induced by abdominal aorta coarctation and 33 sham-operated rats were divided into 6 groups according to trans-mitral flow patterns.MethodsConventional echocardiography, TDI, and IVPG sampling were performed on rats under general anesthesia with 2.5% isoflurane at 3 weeks after the operation. After code EA-separation = 1, EA-half-separation = 2, and EA-fusion = 3, Pearson’s correlation tests were performed.ResultsBoth E and E’ in EA-fusion (1.04 ± 0.13 and 7.65 ± 0.84) are higher than the EA-separation pattern in all rats (0.91 ± 0.10 and 5.51 ± 0.78, p < 0.001). The preload change has more impact on E’ than E (0.443 vs. 0.218, p < 0.001, respectively), which leads to decreased E/E’ in EA-fusion. Total IVPG and basal IVPG positively correlated with the mitral inflow pattern (0.265 and 0.270, p < 0.001), while mid-to-apical IVPG was not (0.070, p = 0.281).ConclusionThe mitral inflow pattern positively correlates with basal IVPG, E, and E’. Mid-to-apical IVPG was independent of mitral inflow patterns, while E/E’ tended to be lower when the mitral inflow pattern changed from EA-separation to EA-fusion.